Commercial Release of Genetically Modified Crops in Africa: Interface Between Biosafety Regulatory Systems and Varietal Release Systems - Akinbo, Olalekan; Obukosia, Silas; Ouedraogo, Jeremy; Sinebo, Woldeyesus; Savadogo, Moussa; Timpo, Samuel; Mbabazi, Ruth; Maredia, Karim; Makinde, Diran; Ambali, Aggrey (Frontiers in Plant Science, 2021)
African countries face key challenges in the deployment of GM crops due to incongruities in the processes for effective and efficient commercial release while simultaneously ensuring food and environmental safety. Against the backdrop of the preceding scenario, and for the effective and efficient commercial release of GM crops for cultivation by farmers, while simultaneously ensuring food and environmental safety, there is a need for the close collaboration of and the interplay between the biosafety competent authorities and the variety release authorities. The commercial release of genetically modified (GM) crops for cultivation requires the approval of biosafety regulatory packages. The evaluation and approval of lead events fall under the jurisdiction of competent national authorities for biosafety (which may be ministries, autonomous authorities, or agencies). The evaluation of lead events fundamentally comprises a review of environmental, food, and feed safety data as provided for in the Biosafety Acts, implementing regulations, and, in some cases, the involvement of other relevant legal instruments. Although the lead GM event may be commercially released for farmers to cultivate, it is often introgressed into locally adapted and farmer preferred non-GM cultivars that are already released and grown by the farmers. The introduction of new biotechnology products to farmers is a process that includes comprehensive testing in the laboratory, greenhouse, and field over some time. The process provides answers to questions about the safety of the products before being introduced into the environment and marketplace. This is the first step in regulatory approvals. The output of the research and development phase of the product development cycle is the identification of a safe and best performing event for advancement to regulatory testing, likely commercialization, and general release. The process of the commercial release of new crop varieties in countries with established formal seed systems is guided by well-defined procedures and approval systems and regulated by the Seed Acts and implemented regulations. In countries with seed laws, no crop varieties are approved for commercial cultivation prior to the fulfillment of the national performance trials and the distinctness, uniformity, and stability tests, as well as prior to the approval by the National Variety Release Committee. This review outlines key challenges faced by African countries in the deployment of GM crops and cites lessons learned as well as best practices from countries that have successfully commercialized genetically engineered crops.